Constructing domestic retrofit as a new urban infrastructure: experimentation, equitability and contested priorities. Issue 9 (2nd September 2019) - Ince, Rebecca; Marvin, Simon
ABSTRACT: British cities and residential suburbs were originally developed under a modernist growth logic: separating home from work, with little concern for energy use. But recent political and social priorities such as climate change and energy security have created an imperative to reduce domestic energy use, with many existing dwellings rendered "obsolete" on account of their poor energy efficiency. This precipitated a need to develop domestic retrofit – the modification of building fabrics and systems to improve their energy efficiency – as an urban infrastructure. The UK Government responded in 2011 with policies such as the "Green Deal", through which coalitions of actors in cities including local authorities, voluntary sector organisations and private businesses were encouraged to experiment with place-based retrofit. This paper examines the challenges and effects of developing a domestic retrofit infrastructure in a North London borough under particularly challenging policy conditions. We develop a hybrid framework for understanding the process and product of this place-based experimentation and through this we ask two questions: 1. How did both local and national conditions enable and limit the development of this infrastructure? 2. Was the emerging urban infrastructure functional and equitable? In Haringey's case, a strong local political agenda positioned retrofit as a development opportunity and vehicle for reducing inequality, but national priorities around market-making and technological fixes dominated emerging responses. Whilst Haringey's efforts in a difficult policy context did result in retrofits and improvements to around a thousand properties, the emerging infrastructure of retrofit services was incomplete, inequitable and temporary.